SISTEM PENDETEKSI DINI PLAGIARISME MENGGUNAKAN ALGORITMA LEVENSHTEIN DISTANCE - Febiawan, Muhamad Hendra; Setiawan, Agus; Primadewi, Ardhin (Jurnal Komtika (Komputasi dan Informatika), 2019)
The academic world in Indonesia has growing rapidly which is marked by the development of science and technology. With all the facilities offered, technology has a positive and negative impact on life. One of negative impacts is plagiarism. The plagiarism often occurs among students, therefore detection of plagiarism needs to be done to avoid plagiarism. This reseacrh to detect the similarity of the text content of the document using the Levenshtein Distance algorithm. The type of document used is .pdf . The documents used are thesis proposals and publication papers. In the calculation speed test, the source document which count words 4405 with 3 comparative documents that have words 13465 count produces a calculation duration 3.57 seconds.